Community Nursing Care: Unhealthy Lifestyle as A Risk Factor of Hypertension in Older Adults in Rural Areas - Nurrahmawati, Marsya; Rasni, Hanny; Lindawati, Revy Dwi Citra (Jurnal Kesehatan Komunitas Indonesia, 2024)
Introduction:  Adults-elderly habits of unhealthy lifestyles increase the risk of hypertension. The high incidence of hypertension causes indications for the diagnosis of community health deficit. Hypertension can be associated with heredity, an unhealthy lifestyle such as smoking, less consumption of vegetables and fruits, lack of physical activity, alcohol consumption and stress. Objective: to determinan the picture of community nursing care, unhealthy lifestyles health deficit problems in older adults with behavioral promotion interventions for health efforts in RW 02 Baratan Village. Method: The method use in this study was quantitative descriptive and quota sampling technique to determine the sample. Results: The research results show that implementig promotion interventions for health efforts are able to increase knowledge, atttudes, and behavior towards healthy lifestyles through education programs, exercise, and demonstrations. The Sig(2-tailed) value obtained in the knowledge category was P=0.025; attitude category P=0.000; behavior category P=0.000 where a<0.05 means there is a difference between before and after implementation. Conclusion: There has been increase in health program participation, health standars compliance, and monitoring of communty health standards.